Students’ Cohesion Used by Eleventh Graders in Writing Report Text (RETAIN, 2020)
Abstract One of the hardest skills in English is writing. Students need time for being able to write well. Because writing is a composition with many principles in it. There are some components in writing in order to make a well composition. One of the components is cohesion and it needs cohesive devices to fulfil. Cohesive devices have four components, they are conjunctions, definite article, personal pronouns, and demonstrative pronouns. The aim of this research is to know how the students of eleventh grade use cohesive devices in their writing report text. This research uses qualitative as the research design and explains descriptively. The research takes place in SMAN 1 Kediri and the students of eleventh grade as the subject of the study. The researcher does document analysis by analysing students’ writing by looking at the cohesive devices that are used. The data are analysed by reducing data, displaying data, and making conclusion. The result is the students of eleventh grade used cohesive devices n their writing report text quite well. Most of them used all cohesive devices to make their writing looks good. Although, one component of cohesive devices was used a little by the students, their writing still consists one or two of it. Finally, the students use cohesive devices in their writing report text although the teacher did not explain about it.